Răspuns :
x² - 6x + 8 = 0
Δ = 36 - 32 = 4
x1 = (6 + 2)/2 = 8/2 = 4
x2 = (6-2)/2 = 4/2 = 2
S = {2; 4}
x² + 3x - 40 = 0
Δ = 9 + 160 = 169
x1 = (-3 + 13)/2 = 10/2 = 5
x2 = (-3 - 13)/2 = -16/2 = -8
S= {-8; 5}
5x² - 4x - 12 = 0
Δ = 16 + 240 = 256
x1 = (4 + 16)/ 10 = 20/10 = 2
x2 = (4 - 16)//10 = - 12/10 = -6/5
S = {-6/5; 2}
9x² - 12x + 4 = 0
Δ = 144 - 144 = 0
cand Δ = 0 , x1,2 = -b/2a
x1,2 = 12/18 = 2/3
Δ = b² - 4ac
x1,2 = (-b +-√Δ) / 2a
Δ = 36 - 32 = 4
x1 = (6 + 2)/2 = 8/2 = 4
x2 = (6-2)/2 = 4/2 = 2
S = {2; 4}
x² + 3x - 40 = 0
Δ = 9 + 160 = 169
x1 = (-3 + 13)/2 = 10/2 = 5
x2 = (-3 - 13)/2 = -16/2 = -8
S= {-8; 5}
5x² - 4x - 12 = 0
Δ = 16 + 240 = 256
x1 = (4 + 16)/ 10 = 20/10 = 2
x2 = (4 - 16)//10 = - 12/10 = -6/5
S = {-6/5; 2}
9x² - 12x + 4 = 0
Δ = 144 - 144 = 0
cand Δ = 0 , x1,2 = -b/2a
x1,2 = 12/18 = 2/3
Δ = b² - 4ac
x1,2 = (-b +-√Δ) / 2a